Pelatihan Basic Human Factor untuk Peningkatan Self Awareness dan Safety Culture Petugas Operasi Bandar Udara Gusti Syamsir Alam - Direstu Amalia; Wildan Nugraha; Viktor Suryan; Virma Septiani; Belen Sri H Napitulu (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2020)
The study of human factors is about understanding human behavior and performance. When applied to flight operations, human factors are used to optimize the relationship between humans and the system they work in to improve safety and performance. An overview of the effects of human factors in aviation and the importance of self-awareness will be explained in this training. Satisfactory training results were achieved by 16 people, 8 very good people, and 2 people with good credentials with the highest score range of 94.70 and the lowest score of 74.25.